Ultrasound-Promoted Degradation of Acid Brown 348 by Fenton-Like Processes - Li, Ji-Tai; Lan, Rui-Jia; Bai, Bo; song, Ya-Li (Asian Journal of Chemistry, 2012)
The combination of ultrasonic irradiation and Fenton-like's reagent is effective for the degradation of Acid brown 348 in aqueous solution. Furthermore, it can achieve better results than either Fenton-like reagent or ultrasound alone. Effects of the reaction conditions on the removal of Acid brown 348 from aqueous solution were observed under ultrasound irradiation. The best removal ratio was 96 % under the optimal conditions (pH 2.5, dosage of fly ash 2.5 g/L, H2O2 5.0 mM, the dye initial concentration 50 mg/L, temperature 40 ºC, reaction time 140 min, ultrasonic frequency 40 kHz). Based on the degradation compounds identified from LC-MS and UV-VIS studies, -N=N- bonds of the Acid brown 348 molecule were found to be broken. The wastewater from the factory was treated first by activated carbon absorption and then degraded with ultrasound/fly ash/H2O2, the removal efficiency of CODCr of dye wastewater was 95 %, whose degradation kinetic was well fitted Behnajady's model.